Review of Internet of Things (IoT) and Blockchain In Healthcare: Chronic Disease Detection and Data Security - Rubaeah, Siti; Mangkunegara, Iis Setiawan; Purwono, Purwono (Journal of Advanced Health Informatics Research, 2023)
The role of Internet of Things (IoT) technology continues to increase in various fields, especially health. IoT can connect doctors with their patients via the Internet. Portable IoT-based health monitoring devices can significantly reduce the distance between patients and doctors. The important influence of IoT technology in the health sector can be seen from its efficiency and important role in developing and improving the quality of health services. IoT is the last Internet revolution that allows integrity between machines and objects. Developers and users still have to pay attention to data security, considering that medical history is a matter of privacy for some people. Blockchain technology has been predicted by the industry and research community as a secure, fast, reliable and transparent solution for IoT-based systems. Most blockchain technology is used for data management operations in the IoT-based health sector, which improves data security, including data integrity, access control, and maintenance of privacy.